(3JeGe GdeJhf aj TQM QSGdI GHf RjOhfs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj, UdGM GdOjf , J (B764 (3g` s; (3GHf RjOhf , CHh GdhdjO CMeO Hf YHO Gddg Hf ZGdH Hf RjOhf GdeNRhej GdCfOdSj, CHh GdhdjO,J (B463 (3g` s ((3YeQ Hf YKeGf Hf GdMdja s)
(3ChdgG (B:s
(3hHYO aEf QSGdI GHf RjOhf GdJi cJHgG dGHf LghQ ef GdQGSGFd GdWfGfI adPdc BKQJ Cf Cedi YdjgG TQMG hCHfi Ydi chGcH chGYHgG UQMG hHGddg CYJUe hCYJVO s
(3BNQgG (B:s
(3agH GdUaM dGYOeJc ehdi OGHfGf geGe hHQYeje s
(3hgj GdQSGdI GdJgcejI GdJi cJHgG GHf RjOhf dGHf LghQ hgj ZjQ QSGdJg GdJi cJHJgG Edi CHj YGeQ Ydi dSGf hdGOI HfJ GdeJcai HGddg GdJi TQMgG GHf fHGJgs
(3Yf fSNI CNQi HNW GdeUfas
(3hHGdfSNI HYV VHW hGdhQbI GdChdi HNW eZGjQs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs